2019
DOI: 10.5194/amt-12-1409-2019
|View full text |Cite
|
Sign up to set email alerts
|

Dual-wavelength radar technique development for snow rate estimation: a case study from GCPEx

Abstract: Abstract. quantitative precipitation estimation (QPE) of snowfall has generally been expressed in power-law form between equivalent radar reflectivity factor (Ze) and liquid equivalent snow rate (SR). It is known that there is large variability in the prefactor of the power law due to changes in particle size distribution (PSD), density, and fall velocity, whereas the variability of the exponent is considerably smaller. The dual-wavelength radar reflectivity ratio (DWR) technique can improve SR accuracy by est… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Several studies suggested utilizing the dual-wavelength ratio (DWR) for improving the accuracy of radar-based quantitative precipitation estimation (QPE) for snowfall and for retrieving microphysical properties of ice hydrometeors values (e.g., Matrosov 1998;Liao et al 2005;Huang et al 2019). Some studies extended this by using triple-frequency measurements for deriving two different DWR values (e.g., Kneifel et al 2015;Chase et al 2018;Leinonen et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies suggested utilizing the dual-wavelength ratio (DWR) for improving the accuracy of radar-based quantitative precipitation estimation (QPE) for snowfall and for retrieving microphysical properties of ice hydrometeors values (e.g., Matrosov 1998;Liao et al 2005;Huang et al 2019). Some studies extended this by using triple-frequency measurements for deriving two different DWR values (e.g., Kneifel et al 2015;Chase et al 2018;Leinonen et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Because DWR depends on hydrometeor shape (Matrosov 1993;Matrosov et al 2005), snowfall property retrieval techniques utilizing the DWR usually assume an average ice hydrometeor shape (e.g., Mason et al 2018;Huang et al 2019). The shape parameter is usually expressed as a particle aspect ratio, which is defined as a ratio of hydrometeor minor and major dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…Radars can measure larger areas and thus provide more accurate QPE. There have been lots of snowfall rate estimations based on radar in the past (Bukovcic et al 2018;Hassan et al 2017;Huang et al 2010;Huang et al 2015;Huang et al 2019;Souverijns et al 2015;von Lerber et al 2017), and the majority of them use power-law relations between liquid water equivalent snowfall rate (S) and equivalent radar reflectivity factor (herein Z), = . Due to various reasons the prefactor and exponent vary greatly and cause large difference in snowfall estimation.…”
Section: Introductionmentioning
confidence: 99%
“…The use of DFR (the ratio of reflectivity at Ku-band and Ka-band) to estimate snowfall rate is considered here to reduce errors. Research using dual-frequency radar for snow quantitative precipitation estimation (QPE) is rare (Huang et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…many ice studies before. Matrosov (1998) developed a DWR method to estimate the snowfall rate R, supplementing experimental Ze-R relations with a retrieved median size, while in Huang et al (2019) the DWR was used for Quantitative 80 Precipitation Estimation (QPE) from the combination of Ku-and Ka-band which were accounted to be Rayleigh and Mie region, respectively, for the detected particles sizes. In other studies, such as Hogan and Illingworth (1999) and Hogan et al (2000), DWR from airborne and ground-based radars was used to estimate ice crystals sizes as well as IWC for cirrus clouds.…”
Section: Introductionmentioning
confidence: 99%